EFL Students' Practices of Self-Regulated Language Learning in Speaking - Halim, Abdul; Atikah, Dewi; Yang, Chen Ching; Rahayu, Sri (Langkawi: Journal of The Association for Arabic and English, 2023)
This study investigates the self-regulation strategies employed by English as a Foreign Language (EFL) students to augment their speaking proficiency. Grounded in Bandura's social cognitive theory and Zimmerman's metacognitive approach, this research adopted a case study research design to capture the essence of participants' experiences. Findings revealed a diverse array of highly effective self-regulation strategies, including reading practice, video consumption, engaging in speaking exercises, writing tasks, note-taking, listening to English content, and maintaining a healthy lifestyle. Reading practice emerges as a foundational strategy. Its emergence allows students to expand their vocabulary, develop critical thinking skills, and broaden their perspectives. Watching videos is a potent tool for language development, enabling students to acquire new vocabulary, refine pronunciation, and observe effective body language. Speaking practice provides a platform for students to apply their knowledge in verbal communication, resulting in enhanced vocabulary retention, pronunciation, and body language skills. These strategies empowered students to expand vocabulary, develop critical thinking skills, refine pronunciation, and enhance body language. The study aligns with prior research and offers a comprehensive framework for EFL learners to optimize their language acquisition process. Pedagogically, the identified strategies provide educators, curriculum designers, and policymakers in English Language Teaching (ELT) with valuable insights to create learner-centered environments. By integrating these strategies, educators can foster independent, motivated learners, curriculum designers can embed effective self-regulation techniques, and policymakers can advocate for learner-centered approaches. This integration can potentially revolutionize ELT, producing empowered, independent learners poised for success in language acquisition and lifelong learning endeavors.